On Some Identities of Balancing-Like and Lucas-Balancing-Like Sequences by the Matrix Method - Ritthidej, Sanit; Buatong, Theerapon; Tipsri, Sirachat (PKRU SciTech Journal, 2023)
Balancing-like and Lucas-balancing-like sequences are defined by and for positive integer , respectively, for and are solutions of Pell’s equation . These sequences are determined as the linear recurrence relations and with initial conditions and for positive integer , respectively. In this paper, some identities of Balancing-like and Lucas-balancing-like sequences are obtained by using Binet’s formulas which are formulated by matrices and .